The microstructure and the mechanical property of AZ91D solidified under GPa-grade high-pressure. Issue 14 (22nd September 2019) - Lin, Wang; Xiaoping, Lin; Chang, Xu; Shengshi, Zhao; Heng, Sun; Ning, Zhang
ABSTRACT: High-pressure (2–4 GPa) solidified AZ91D alloy was prepared and the microstructure was investigated by X-ray energy diffraction and scanning electronic microscopy. The room-temperature compression deformation behaviour was also studied. The results showed that the high-pressure solidified AZ91D alloy was composed of nanometre β-Mg17 Al12 and equiaxed α-Mg dendrites. The average size of α-Mg grains decreased from 395 ± 5 µm (atmosphere pressure) to 12 ± 3 µm (4 GPa) and the solubility of Al in α-Mg increased to 6.25 wt-% at 4 GPa. The compression strength of 402 MPa and the relative compression ratio of 27% (4 GPa) were 50% and 93% higher than the original AZ91D. Meanwhile, high pressure can also decreased the corrosion rate from 0.0675 mA/cm 2 (atmosphere pressure) to 0.0122 mA/cm 2 (4 GPa).